Modeling Retinitis Pigmentosa: Retinal Organoids Generated From the iPSCs of a Patient With the USH2A Mutation Show Early Developmental Abnormalities - Guo, Yonglong; Wang, Peiyuan; Ma, Jacey Hongjie; Cui, Zekai; Yu, Quan; Liu, Shiwei; Xue, Yunxia; Zhu, Deliang; Cao, Jixing; Li, Zhijie; Tang, Shibo; Chen, Jiansu (Frontiers in Cellular Neuroscience, 2019)
Retinitis pigmentosa (RP) represents a group of inherited retinopathies with early-onset nyctalopia followed by progressive photoreceptor degeneration causing irreversible vision loss. Mutations in USH2A are the most common cause of nonsyndromic RP. Here, we reprogrammed induced pluripotent stem cells (iPSCs) from a RP patient with a mutation in USH2A (c.8559-2A>G/c.9127_9129delTCC). Then, multilayer retinal organoids including neural retina (NR) and retinal pigment epithelium (RPE) were generated by three-step “induction-reversal culture”. The early retinal organoids derived from the RP patient with the USH2A mutation exhibited significant defects in terms of morphology, immunofluorescence staining and transcriptional profiling. To the best of our knowledge, the pathogenic mutation (c.9127_9129delTCC) in USH2A has not been reported previously among RP patients. Notably, the expression of laminin in the USH2A mutation organoids was significantly lower than in the iPSCs derived from healthy, age- and sex-matched controls during the retinal organogenesis. We also observed that abnormal retinal neuroepithelium differentiation and polarization caused defective retinal progenitor cell development and retinal layer formation, disordered organization of neural retinas in the presence of the USH2A mutation. Furthermore, the USH2A mutation bearing RPE cells presented abnormal morphology, lacking pigmented foci and showing an apoptotic trend and reduced expression of specific makers, such as MITF, PEDF and RPE65. In addition, the USH2A mutation organoids had lower expression of cilium-associated (especially CFAP43, PIFO) and dopaminergic synapse-related genes (including DLGAP1, GRIK1, SLC17A7 and SLC17A8), while there was higher expression of neuron apoptotic process-related genes (especially HIF1A, ADARB1 and CASP3). This study may provide essential assistance in the molecular diagnosis and screening of RP. This work recapitulates the pathogenesis of USH2A using patient-specific organoids and demonstrated that alterations in USH2A function due to mutations may lead to cellular and molecular abnormalities.